Volatile-mediated interactions between phylogenetically different soil bacteria - Garbeva, Paolina; Hordijk, Cornelis; Gerards, Saskia; de Boer, Wietse (Frontiers in Microbiology, 2014)
There is increasing evidence that organic volatiles play an important role in interactions between micro-organisms in the porous soil matrix. Here we report that volatile compounds emitted by different soil bacteria can affect the growth, antibiotic production and gene expression of the soil bacterium Pseudomonas fluorescens Pf0-1. We applied a novel cultivation approach that mimics the natural nutritional heterogeneity in soil in which P. fluorescens grown on nutrient-limited agar was exposed to volatiles produced by 4 phylogenetically different bacterial isolates (Collimonas pratensis, Serratia plymuthica, Paenibacillus sp. and Pedobacter sp.) growing in sand containing artificial root exudates. Contrary to our expectation, the produced volatiles stimulated rather than inhibited the growth of P. fluorescens. A genome-wide, microarray-based analysis revealed that volatiles of all 4 bacterial strains affected gene expression of P. fluorescens, but with a different pattern of gene expression for each strain. Based on the annotation of the differently expressed genes, bacterial volatiles appear to induce a chemotactic motility response in P. fluorescens, but also an oxidative stress response. A more detailed study revealed that volatiles produced by C. pratensis triggered, antimicrobial secondary metabolite production in P. fluorescens. Our results indicate that bacterial volatiles can have an important role in communication, trophic - and antagonistic interactions within the soil bacterial community.